2004
DOI: 10.1161/01.hyp.0000120155.48024.6f
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Potassium Excretion and Sodium Sensitivity in Blacks

Abstract: Abstract-Based on racial differences in urinary potassium excretion and responses to diuretics, we present a model suggesting that a major cause of sodium sensitivity in blacks is an augmented activity of the Na-K-2Cl cotransport in the thick ascending limb of Henle's loop. This would result in an increased ability to conserve not only sodium but also water, and an upward and rightward shift in the operating point of tubuloglomerular feedback, which may cause an increase in the glomerular capillary hydraulic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 75 publications
3
91
0
Order By: Relevance
“…35 We also observed that plasma sodium concentrations were lower in the blacks. Also consistent with previous observations of others, 36 in the current study, plasma AVP concentrations were higher in the blacks, and conceivably this may account for the lower serum sodium concentrations.…”
Section: Grim Et Al Aldosterone and Hypertension 769supporting
confidence: 52%
“…35 We also observed that plasma sodium concentrations were lower in the blacks. Also consistent with previous observations of others, 36 in the current study, plasma AVP concentrations were higher in the blacks, and conceivably this may account for the lower serum sodium concentrations.…”
Section: Grim Et Al Aldosterone and Hypertension 769supporting
confidence: 52%
“…18,19 Aviv et al 20,21 reviewed previously reported clinical studies that indicated that the thick ascending limb (TAL) had a pivotal role in the susceptibility of Blacks to HTN. A mechanism was proposed in which an increase in NKCC2 activity could lead to the expansion of the extracellular volume and thus be associated with HTN.…”
Section: Discussionmentioning
confidence: 99%
“…The common variants of the UMOD promoter will influence the mRNA level and thus regulate the expression/ secretion of UMOD in the renal TALs. The renal TALs have important roles in sodium reabsorption, 20,21 and UMOD may regulate sodium reabsorption in this tissue 24 and thus regulate BP. One of our results appeared to be contradicted by previous studies, indicating that the real mechanism of UMOD in the regulation of BP needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…This topic is addressed in detail in a recent communication. 16 The mechanism that accounts for the effect of potassium supplementation on ADP-evoked platelet aggregation is unclear. We suspect that this phenomenon may ultimately relate to the link between the sodium/potassium gradients across the platelet plasma membrane and platelet cytosolic calcium, which is the penultimate platelet activator.…”
Section: Kimura Et Al Potassium and Platelet Reactivity 971mentioning
confidence: 99%